Properties of lotus seed starch-glycerin monostearin V-complexes after long-term retrogradation. (1st May 2020) - Zheng, Yixin; Wang, Bailong; Guo, Zebin; Zhang, Yi; Zheng, Baodong; Zeng, Shaoxiao; Zeng, Hongliang
Highlights: LS with GMS improved formation of crystallinity and an ordered structure of starch. V6I -complexes had superior ability to enhance water retention of starch than V6II . V-complexes inhibited aggregation of molecular chain and changed it to nanoscale. V-complexes improved heat sensitivity and flow behavior than other crystal samples. V-complexes with great water retention improved physicochemical properties. Abstract: The properties of lotus seed starch-glycerin monostearin with V6II and V6I -complexes formed at 50 MPa and 100 MPa after long-term retrogradation (named as LS-GMS-50 and LS-GMS-100, respectively) were investigated. The results indicated LS-GMS-50 and LS-GMS-100 were conducive to the formation of crystallinity and an ordered structure of starch compared to lotus seed, lotus seed at 50 MPa and 100 MPa (LS, LS-50 and LS-100), especially V6I -complexes. The presence of V6I -complexes had the superior ability to enhance water retention of starch gel compared to V6II -complexes. V-complexes inhibited the aggregation of molecular chain and changed the molecular chain to nanoscale, especially V6I -complexes. Moreover, physicochemical properties demonstrated V-complexes lowered thermal enthalpy value and heat sensitivity compared to other samples. Rheological measurement showed V-complexes improved the flow behavior and viscoelasticity of retrograded starch. Thus, a formation mechanism was that V-complexes improved the internal network structure and freed up space to store water molecules.